THE IMPACT OF ARTIFICIAL INTELLIGENCE ON ENGLISH LANGUAGE TEACHING AND LEARNING - Urinbekova Ezozakhon Uchqunovna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract.  This  article  examines  the  impact  of  artificial  intelligence  (AI)  on English  language  teaching  and  learning  in  contemporary  educational  settings.  It discusses the role of AI in personalizing instruction, improving language assessment, enhancing  speaking,  writing,  reading,  and  vocabulary  acquisition,  and  supporting teachers  through  intelligent  educational  technologies.  The  article  also  explores  the advantages,  challenges,  and  future  prospects  of  AI  integration  in  English  language education. It concludes that AI serves as an effective educational tool that enhances learning outcomes while complementing, rather than replacing, the role of teachers.